2015
DOI: 10.3389/fpls.2015.00945
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative genetic analysis of agronomic and morphological traits in sorghum, Sorghum bicolor

Abstract: The productivity in sorghum is low, owing to various biotic and abiotic constraints. Combining insect resistance with desirable agronomic and morphological traits is important to increase sorghum productivity. Therefore, it is important to understand the variability for various agronomic traits, their heritabilities and nature of gene action to develop appropriate strategies for crop improvement. Therefore, a full diallel set of 10 parents and their 90 crosses including reciprocals were evaluated in replicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…are theoretically determined by both maternal (nuclear and cytoplasmic) and zygotic (embryo and endosperm) effects. The genetic analyses of reciprocal crosses in several species, including Arabidopsis (Alonso‐Blanco et al ., ), maize (Seka and Cross, ; Zhang et al ., ), wheat (Minhas et al ., ), cotton (Pahlavani and Abolhasani, ), peanut (Hariprasanna et al ., ), sorghum (Mohammed et al ., ), pea (Lemontey et al ., ) and bean (Duc et al ., ; Singh et al ., ), have shown that both maternal and xenia (via zygote) effects have significant roles on seed size/weight. However, the relative importance of maternal and zygotic effects has not been analyzed and thus is unclear in rapeseed, in spite of its fundamental interest and significance in genetic study and breeding.…”
Section: Introductionmentioning
confidence: 99%
“…are theoretically determined by both maternal (nuclear and cytoplasmic) and zygotic (embryo and endosperm) effects. The genetic analyses of reciprocal crosses in several species, including Arabidopsis (Alonso‐Blanco et al ., ), maize (Seka and Cross, ; Zhang et al ., ), wheat (Minhas et al ., ), cotton (Pahlavani and Abolhasani, ), peanut (Hariprasanna et al ., ), sorghum (Mohammed et al ., ), pea (Lemontey et al ., ) and bean (Duc et al ., ; Singh et al ., ), have shown that both maternal and xenia (via zygote) effects have significant roles on seed size/weight. However, the relative importance of maternal and zygotic effects has not been analyzed and thus is unclear in rapeseed, in spite of its fundamental interest and significance in genetic study and breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum ( Sorghum bicolor L., 2 n = 20), which belongs to the Poaceae family, is a C4 crop plant that is cultivated for seeds, sugar and green biomass used as forage (Carpita and McCann 2008 ; Mohammed et al 2015 ). Recently, sorghum was used for biofuel production, and it is a model bioenergy plant (Calvino and Messing 2012 ; Mullet et al 2014 ; Vermerris 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sorghum is considered one of the most drought-resistant and heat tolerant agricultural crops in world agriculture [1]. In terms of world grain production, sorghum ranks fifth after wheat, rice, corn and barley [2,3].…”
Section: Introductionmentioning
confidence: 99%